Leadership skill, leadership style and job commitment among academic staff of Nigerian universities: the moderating effects of employee's attitude and work environment - Isidore Ekpe; Norsiah Mat; Mary Olufunmilayo Adelaiye (Inderscience Online, 2017)
The study aims to determine the moderating effects of employee’s attitude and work environment on the relationship between leadership skill and leadership style, and employee’s job commitment among academic staff of Nigerian universities. The results of this study would enable the Nigerian government to develop strategies to help lecturers develop more interest in research. The study employs cross-sectional survey design, with simple random sampling, to collect data from 340 academic staff of three universities in the northern, eastern and western regions of Nigeria. Descriptive statistics and Partial Least Square (Smart PLS) were used to analyse data. The results indicate that transformational leadership style is positively related to employee’s job commitment and that attitude moderates between transactional leadership style and employee’s job commitment. The study suggests that appropriate leadership (from heads of departments) and adequate funding (from government) could engender more research commitments among scholars at Nigerian universities.